If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5) + -2(3 + -4x) = 4(x + 5) + -1 Reorder the terms: (5 + x) + -2(3 + -4x) = 4(x + 5) + -1 Remove parenthesis around (5 + x) 5 + x + -2(3 + -4x) = 4(x + 5) + -1 5 + x + (3 * -2 + -4x * -2) = 4(x + 5) + -1 5 + x + (-6 + 8x) = 4(x + 5) + -1 Reorder the terms: 5 + -6 + x + 8x = 4(x + 5) + -1 Combine like terms: 5 + -6 = -1 -1 + x + 8x = 4(x + 5) + -1 Combine like terms: x + 8x = 9x -1 + 9x = 4(x + 5) + -1 Reorder the terms: -1 + 9x = 4(5 + x) + -1 -1 + 9x = (5 * 4 + x * 4) + -1 -1 + 9x = (20 + 4x) + -1 Reorder the terms: -1 + 9x = 20 + -1 + 4x Combine like terms: 20 + -1 = 19 -1 + 9x = 19 + 4x Solving -1 + 9x = 19 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -1 + 9x + -4x = 19 + 4x + -4x Combine like terms: 9x + -4x = 5x -1 + 5x = 19 + 4x + -4x Combine like terms: 4x + -4x = 0 -1 + 5x = 19 + 0 -1 + 5x = 19 Add '1' to each side of the equation. -1 + 1 + 5x = 19 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 19 + 1 5x = 19 + 1 Combine like terms: 19 + 1 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| -4=-6n-(6n-2) | | 8x+-8=x+7 | | 4(x+2)+6x=20 | | 2x-1overx=-1 | | -6/5*30 | | -50y=3y-8 | | 2c^3-4c^2-70c=0 | | 2(x-2)+x+x+3=25 | | 5n-16=8n-10 | | 2*ln(x+1)=ln(2x) | | 2x^2+28x+103=30 | | 15x-20=8x+16+5 | | 2+-3/4=6 | | [s+3(s-1)]=18 | | 5/7/35 | | 10-1/2x=6x-3 | | 18+c/4=32 | | 18+c/4=32 | | -6.8-(-6.4)= | | (X+2)-2(2-2x)=2(x+4)-1 | | 28000n+3000n=36000n+2000n | | -3*(h-6)=5*(2h+3) | | 6(x+5)*4=3x-5 | | 0.5x+0.5=x+1 | | 4+-45= | | 16/4/5 | | 7+6x=4x-13 | | -3x^2-7x+5= | | 40+x=60 | | 15-4z=10 | | 13-19.2= | | 2c(c-8)=0 |